Application of microwave surgical instrument to lung segmentectomy for small-sized lung cancerCentral MessagePerspective - Takeshi Mimura, MD, PhD; Masayuki Ishida, MD; Kazuki Tadokoro, MD; Atsushi Kamigaichi, MD; Yuya Hirai, MD; Mai Nishina, MD; Atsushi Kagimoto, MD, PhD; Norifumi Tsubokawa, MD, PhD; Yoshinori Yamashita, MD, PhD (JTCVS Techniques)
Objectives: For lung segmentectomy of small lung cancers, we used a microwave surgical instrument for lung parenchymal dissection mainly at the pulmonary hilum, which is difficult to handle with surgical staplers. This technique facilitated the insertion of staples. Methods: In total, 116 patients with cStage 0-1A3 non–small cell lung cancer who underwent lung segmentectomy were included in this study. We compared the perioperative factors of the group in which a microwave surgical instrument was used for dissection procedures, including lung parenchymal dissection at the pulmonary hilum, and peripheral intersegmental dissection was performed with surgical staplers (group M+S: N = 69), with those of the group in which parenchymal dissection was performed mainly with surgical staplers without using the microwave surgical instrument (group S: N = 47). Results: Although more complex segmentectomies were performed in the M+S group (P = .001), the number of staple cartridges (7 staple cartridges vs 8 staple cartridges, P = .005), the surgical times (179 vs 221 minutes, P < .0001), and the blood loss (5 mL vs 30 mL, P = .012) were significantly lower in the M+S group. The duration of chest tube placement was significantly shorter in the M+S group (P = .019), and postoperative complications of grade 2 or greater were significantly lower in the M+S group (P = .049). Conclusions: The effective use of the microwave surgical instrument combined with surgical staplers can simplify pulmonary hilar and intersegmental plane dissections not only for simple segmentectomy but also for complex segmentectomy, leading to favorable intraoperative and postoperative outcomes.